Tradycja wojny sprawiedliwej a zagadnienie tzw. inwerwencji humanitarnej w prawie międzynarodowym: [Just war tradition and an issue of validity of humanitarian intervention in international law] (Studia Prawnicze / The Legal Studies, 2009)
W niniejszym opracowaniu podjęta zostanie próba oceny przydatności tradycji wojny sprawiedliwej dla uzasadnienia legalności używania siły zbrojnej z pobudek humanitarnych. Uwagazwrócona zostanie na tę część tradycji wojny sprawiedliwej, która dotyczy usprawiedliwiania użycia siły zbrojnej, czyli ius ad bellum.Pojęcie interwencji humanitarnej rozumiane będzie dość wąsko. Swym zakresem obejmie ono nie każde użycie siły zbrojnej przez państwo, grupę państw lub organizację międzynarodową zmierzające do powstrzymania masowych naruszeń praw człowieka w innym państwie, lecz jej użycie z motywów i w celach humanitarnych bez upoważnienia ze strony Rady Bezpieczeństwa ONZ. W literaturzeprzedmiotu określa się często taką interwencję mianem „jednostronnej interwencji humanitarnej”, dla podkreślenia użycia siły zbrojnej nie mieszczącego się wprost w katalogu wyjątków od zakazu używania siły zbrojnej dopuszczanych przez Kartę NZ. The issue of humanitarian intervention and debates about it have become one of the most controversial questions in contemporary ius ad bellum. The aim of the article is to discuss a validity of humanitarian intervention in the context of just war tradition. The prohibition of the threat or use of force contained in Article 2(4) of the United Nations Charter, is currently the subject of fundamental disagreement. There is comparable agreement neither states scholars on the exact scope of the prohibition. Controversies especially concern so-called unilateral humanitarian interventions that is use o force in pursuit of human rights without express authority from the Security Council. The Author argues that just war tradition seems to be an useful tool for solving difficulties surrounding the issue of validity of humanitarian intervention. The just war tradition offers a coexistence of two fundamental values of the international society, that is justice and peace. According to this tradition peace cannot be established without justice, and vice versa justice cannot exist without peace. That is why the tradition can serve as a medium protecting both human rights and international peace and security. Thus one can speak of a „new life” of the just war tradition in today’s international law.